Agro-morphological, glucomannan content and molecular characterization of Malaysian Amorphophallus spp. Blume germplasm collection - Phornvillay, Surisa (2015)
Amorphophallus has attracted much attention as it contains glucomannan and also possess other medicinal properties. Prior to the collection of propagating materials and cultivation, identification and diversity information of the Amorphophallus species are essential as different species perform differently under cultivation. However, limited research has been conducted on morphological and genetic variations of Amorphophallus spp. in Peninsular Malaysia. Therefore, the present study was conducted with objectives, namely collection and establishment of the Amorphophallus spp. in Peninsular Malaysia, morphological and genetic variations, and glucomannan (GM) content of the established Amorphophallus spp. accessions. The current observation from the collection of Amorphophallus spp. from six locations found that Amorphophallus spp. were abundantly spotted in disturbed areas of secondary forest. They were found thriving well in damp, moist and shady areas, mostly near a riverbank. The accessions were established, and their life cycle was observed. Amorphophallus had three distinct growth phases, namely, vegetative, generative and dormancy. The plant had a vegetative growing phase with the leaf development for about 5 months and then underwent a dormancy period for about 2 to 3 months. The plant resumed its growth in the next season or followed by generative life cycle, whereby the inflorescence was produced. Sixty accessions of Amorphophallus spp.,with 10 accessions representing six locations, were used to assess morphological vegetative characters and molecular variations. The morphological variation data were also supplemented with the assessment of 20 Amorphophallus inflorescence accessions. There were variations in morphological characteristics among accessions of Amorphophallus spp. based on corm size, corm shape, cormel number per corm, petiole nature and distinct inflorescence characters, spathe colour, appendix colour and appendix shape and pattern. Genetic variations of the plants were assessed using nine screened microsatellite primers. Principle coordinates and cluster analysis results for morphological and molecular characters clearly separated Kota Bahru, Kelantan (KKB) accessions from the other 50 accessions, thus grouping the accessions into two major groups. The KKB population accounted for 22.22% genetic variations while the remaining five populations varied 77.78 to 100% genetically. Nonetheless, high inbreeding coefficients (0.21 to 0.88) were detected within each of the population. For the determination of glucomannan (GM) content, the 3,5-dinitrosalycyclic acid colorimetric assay was employed. The Hulu Langat, Selangor accession SHL24 was found to contain the highest GM content at 8.29%. The lowest GM content was from Perak, Taiping; PT37 at only 2.55%. The results also showed that there was a significant interaction effect between the populations and the corm size of GM content. Based on the results, PUK population of 500 g had the highest GM content. In conclusions, both the morphology and molecular analysis results suggest that KKB accessions are identified as A. paeoniifolius while other accession are A. prainii particularly based on distinct inflorescence characteristics. This study provides valuable insight and a better understanding of the habitat, growth, phenotypic and genotypic characteristics and GM content of the available Amorphophallus spp. accessions in Peninsular Malaysia. These findings could be used as the basic information for breeding, improvement and conservation program of this plant in Malaysia.